Handbook cobra4 Computer-assisted experiments. Everyday Science, physics, chemistry, biology, tess - Grumann, Markus
Manual
Why do energy-saving lamps need some time to achieve full brightness? .-- Why do light bulbs burn out mostly when being turned on?.-- Sin k or swim?.-- Altitude measurement on a trail.-- Measurement of the height of a tower.-- Terrain mapping.-- What happens during the flash recycling time of a camera?.-- Why do mobile phones or laptops need a charger I adapter? Transportation .-- How can ships made of steel float on water?.-- Mechanics of Liquids and Gases.-- Linear Motion.-- Oscillations.-- Thermodynamics: Heat - A Form of Energy.-- State of Matter.-- Electric Circuits.-- Alternating Current.-- Electronic Components.-- Electrochemistry.-- Ecology: Water.-- Soil.-- Weather and Climate.-- Habitat.-- Mechanics 5.1.1 Forces.-- Heat 5.2.1 Thermal Equilibrium.-- Heat and Internal Energy.-- Change of State: Melting and freezing curve of sodium thiosulphate.-- Electricity I Electronics.-- Electrical Resistance.-- Electric Power and Work.--Capacitors.-- Diodes.-- Electrochemistry.-- The Electric Motor.-- Special Components and Circuits.-- The bridge rectifier
Keywords: Biologia -- pruebas (manual)l); Ciencia -- pruebas (manual); Mecanica -- pruebas (manua; Quimica -- pruebas (manual)